PENELAAHAN SIFAT PRIORITAS PEMANFAATAN JENIS TANAMAN UNTUK KAYU BAKAR - Rachman Effendi; Suwidji Basuki; Han Roliadi (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
There is a need to classify fire wood for flue/ based on energy content. This research is conducted to categorized fire wood species using discriminant analysis.Data of which collected from each of research areas are plant varieties for fire wood, age classification, annual volume increase, specific gravity, calor value and volume of extractive elements.Variety of woods used for fire wood are Akasia (Acacia auriculiformis), Akasia (Acacia decurrens), Kaliandra (Calliandra callothyrsus), Gamal (Gliricidia maculata), Kemlandingan (Leucaena glauca), Turi (Sesbania grandiflora) and Jati (Tectona grandis). For the purpose of analysis of the type of relationship between annual volume increase (X1), specific gravity (X2), calor value (X3), volume of extractive elements (X4) and the adaptation order of plant varieties for fire wood is clasified by the discriminant function.The function is also used for determining adaptation order of utilization of plant varieties for fire wood.Based on the discriminant analysis it can be expressed as:Yj = 0.2148X1j + 9.7184X2j + 0.7231 X3j - 6.7121 X4j..................................................................(1). The result of average substitutions of annual volume increase, as specific gravity, ca/or value increase and volume of extractive elements decreased as described by the equation (I). It can be said that (the adaptation order of plant varieties for fire wood) produced from the most to the least based on its number of heat of combustion at the plantation age 2, 3 and 4 years are Akasia (Acacia decurrens), Akasia (Acacia auriculiformis), Kaliandra (Calliandra callethyrsus), Gamal (Gliricidia maculata), Kemlandingan (Leucaena glauca), Turi (Sesbania grandiflora) and Jati (Tectona grandis).